The laser at 50. - Savage, N.
Fifty years after the first beam of coherent light shone out of a ruby crystal, lasers have expanded in every direction, ranging from as big as three football fields to as small as a few layers of atoms, producing wavelengths from deep in the X-ray regime to far into the infrared. Engineers are pushing the technology ever further, and here are some of the records they have set.